Advanced algorithm UMAC based modular transformations - Евсеев, Сергей Петрович; Король, Ольга Григорьевна; Огурцов, Виталий Вячеславович (Eastern-European Journal of Enterprise Technologies, 2014)
Using modular transformations allows to implement provably secure information hashing, which satisfies the collisional properties of universal hash functions. At the same time, universal hashing using modular transformations has a significant drawback - the high computational complexity of the hash code formation. In fact, it is necessary to perform modular exponentiation for each data block that significantly increases information sequence hashing time under appropriate orders of transformation module. In this regard, the development of multilayer schemes of universal hashing using modular transformations on the last and final stage of the hash code formation is a promising direction. The selection of cycle functions in the scheme of provably secure key universal hashing is substantiated, the model and method for forming control codes of data integrity and authenticity, based on modular transformations, the algorithm for reducing the computational complexity of hashing schemes implementation using cyclic functions, are proposed in the paper. The developed advanced algorithm UMAC provides the required indicators of collisional properties of universal hashing, provable security level and high indicators of the hash code formation speed